2015
DOI: 10.1073/pnas.1424642112
|View full text |Cite|
|
Sign up to set email alerts
|

Inositol pyrophosphates promote tumor growth and metastasis by antagonizing liver kinase B1

Abstract: The inositol pyrophosphates, molecular messengers containing an energetic pyrophosphate bond, impact a wide range of biologic processes. They are generated primarily by a family of three inositol hexakisphosphate kinases (IP6Ks), the principal product of which is diphosphoinositol pentakisphosphate (IP7). We report that IP6K2, via IP7 synthesis, is a major mediator of cancer cell migration and tumor metastasis in cell culture and in intact mice. IP6K2 acts by enhancing cell-matrix adhesion and decreasing cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 42 publications
2
88
0
1
Order By: Relevance
“…This antagonism between upstream and downstream kinases of IP6 metabolism is also found in regulating the tumor suppressor LKB1. Catalytic activity of IPMK activates LKB1 (43), whereas that of IP6K2 suppresses it (44). IP6 plays structural roles in a number of important cellular (23).…”
Section: Discussionmentioning
confidence: 99%
“…This antagonism between upstream and downstream kinases of IP6 metabolism is also found in regulating the tumor suppressor LKB1. Catalytic activity of IPMK activates LKB1 (43), whereas that of IP6K2 suppresses it (44). IP6 plays structural roles in a number of important cellular (23).…”
Section: Discussionmentioning
confidence: 99%
“…5-IP7 may also indirectly inhibit AMPK. For example, 5-IP7 promotes nuclear localization of LKB1 in cancer cells, which diminishes its activity toward the cytosolic targets (80). Cytosolic LKB1 phosphorylates AMPK (81).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shed light on the role of IP 7 in the promotion of tumour growth and metastasis using in vitro and in vivo approaches. 107,108 The Snyder group showed that gene deletion of Ip6k2 in HCT116 human colorectal cancer cells and Ip6k2 knockdown in breast and lung cancer cell lines led to a reduction in focal adhesion kinase (FAK) phosphorylation, correlating with reduced cell spreading and cell-matrix adhesion. 107 Epithelial to mesenchymal transition properties including cell migration and invasion were also significantly reduced in these cells.…”
Section: Actin Cytoskeletonmentioning
confidence: 99%
“…107,108 The Snyder group showed that gene deletion of Ip6k2 in HCT116 human colorectal cancer cells and Ip6k2 knockdown in breast and lung cancer cell lines led to a reduction in focal adhesion kinase (FAK) phosphorylation, correlating with reduced cell spreading and cell-matrix adhesion. 107 Epithelial to mesenchymal transition properties including cell migration and invasion were also significantly reduced in these cells. Subcutaneous xenograft of Ip6k2 knockout HCT116 cells in immune-compromised mice led to tumours that were smaller in size as compared with those formed by parent HCT116 cells.…”
Section: Actin Cytoskeletonmentioning
confidence: 99%